Penerapan Metode Forward Chaining untuk Mendeteksi Penyakit THT - Wiwi Verina (Lembaga Penelitian dan Pengabdian pada Masyarakat (LPPM) STMIK Global Informatika MDP, 2015)
Diseases Ear, Nose and Throathas become adisease that issuffered by the world community. ENT disease progression and higher, it is not accompanied by anumber of experts. In this case, an analysis should be doneto speed up the process of diagnosis. The refore it is necessary to use the expert system is a computer application that behaves like an expert. Expert system capable of solving problems that typically can only be solved by an expert using the knowledge base, facts and reasoning techniques. In this analysis using aforward chaining inference engine. In this approach, starting from the information entered and then draws conclusions, tracking the forefind facts in accordance with the IF-THEN rules. Based on the test system accuracy rate forward chaining method to detect ENT disease that is 100%, which according to the data obtained from the ENT specialist to determine disease based on symptoms exist.